Estimating DNA methylation levels by joint modeling of multiple methylation profiles from microarray data. Issue 2 (4th October 2015) - Wang, Tao; Chen, Mengjie; Zhao, Hongyu
Summary: DNA methylation studies have been revolutionized by the recent development of high throughput array‐based platforms. Most of the existing methods analyze microarray methylation data on a probe‐by‐probe basis, ignoring probe‐specific effects and correlations among methylation levels at neighboring genomic locations. These methods can potentially miss functionally relevant findings associated with genomic regions. In this article, we propose a statistical model that allows us to pool information on the same probe across multiple samples to estimate the probe affinity effect, and to borrow strength from the neighboring probe sites to better estimate the methylation values. Using a simulation study, we demonstrate that our method can provide accurate model‐based estimates. We further use the proposed method to develop a new procedure for detecting differentially methylated regions, and compare it with a state‐of‐the‐art approach via a data application.